Development of automatic cupping suction system (software and circuit) - Yoong, Tai Hui (2022)
Cupping therapy is a traditional healing treatment. It is an ancient form of alternative medicine that can increase blood circulation to the realm where the cup is placed. Traditionally the cups were heated with fire before the open side directly applied to the skin. Some modern cupping practitioners have modernized the way of cupping by using the rubber pumps to create suction on the skin. There are only two main categories of cupping performed today which are dry cupping and wet cupping. A negative pressure is applied on the skin through the suction cup for both cupping method but unregulated pressure that occurred during both methods of cupping might cause blisters or vesicles on the skin. The latest invention of the electric cupping device allows one to perform cupping therapy without a medical certificate. However, it does not support cupping in the hairy skin area. Therefore, an automatic cupping suction system is developed in this project as an effective, efficient and economical automatic system for a better and healthier life. 3 separated automatic cupping system is developed to ensure that multiple cupping process can be handled at the same time and it is able to be activated on the hairy skin area. In designing system, the Arduino board is utilized to develop the automatic system that allows the user to apply cupping therapy by setting the time required. A Fuzzy Logic Controller (FLC) is applying to the program code to ensure the stability of the pressure during the cupping process. The automatic system is created and examined to ensure the system are able to work automatically and to reduce the hazard of getting blister or vesicle. Finally, the automatic system is verified to apply the cupping therapy to the patient effectively.